Colour variation of African bovidae: consequences for conservation and the wildlife ranching industry - Olivier, Phillip Arnold (University of the Free State, 2015)
English: Colour variant game species have become a common sight on game farms and at auctions, as a result of their oddity and high monetary value. Currently there are more than 40 colour variants of African Bovidae. Even though these colour variants have become very sought after and profitable to farm with, it has been warned that colour variants do not contribute to conservation since colour variants normally do not survive in nature. Consequently the intentional breeding of colour variants is causing concern, as they may be a threat to conservation. The objective of this study was to collect data to facilitate decision making in the game ranching and conservation industry. Statistical analysis showed that there were significant behavioural differences between four springbok colour variants studied. Black springbok were less active and utilised much more shaded areas compared to other colour variants or normal coloured animals. The darker coloured animals presented less body surface area to the sun during the warmest times of the day than the white springbok. Springbok were also found to form herds based on phenotype, preferring to associate with homogenous individuals. This phenomenon was likely due to the odd-prey effect. Wildlife auction turnover grew from R62 million to over R1 billion in the last ten years. In conjunction with this growth, record prices for animals are being recorded every year. However in most cases colour variant game are reaching much higher prices than the normal coloured nonspecific's. Colour variants also achieve annual growth which is greater than inflation often providing better return on investment than stock market shares. Even though a normal Kalahari springbok ram set a new record at R1.2 million it was far exceeded by coffee coloured springbok that sold for R4 million. Financial gain then seems to be the main motivator behind the breeding of colour variants as they have become sought after by game ranchers. There is however concern amongst various stakeholders that the breeding of colour variant wildlife is unsustainable. This is as a result of the increasing opposition against the selective breeding of these animals and a general disinterest in these animals from end-users which include hunters and eco-tourists. No significant proof could be found during this study that there will be large-scale interest in the consumptive or non-consumptive use of colour variants. Little published scientific data is available concerning colour variants and most of the available information is in the form of popular magazine articles, newsletters and websites. The lack of published scientific data has resulted in a debate concerning colour variants. Opinions on this issue are much divided and can also evoke strong emotional responses from those involved; particularly from ranchers that are concerned their livelihoods may be threatened by any control measures. Most wildlife ranchers feel that they should be allowed to breed with any animal that provides the best return on investment and that, since colour variants are a natural phenomenon, they do not threaten conservation. Survey results showed that although many respondents did not consider colour variants to be a threat to conservation the majority did not support breeding of such colour variant wildlife. The vast majority of respondents indicated that financial gain was the main reason for the popularity of colour variants. Many stakeholders also expressed great concern about potential damage being done to the conservation and eco-tourism image of South Africa as many, specifically foreign hunters, consider colour variants wildlife to be unnatural. The ultimate conclusion of this study is that the existence of colour variants does not pose a threat to conservation but it is rather the management of these animals which pose a potential threat to conservation of South Africa’s wildlife as well as South Africa’s conservation image.

Afrikaans: Kleur variante van wildspesies het ‘n algemene gesig geword op wildplase en by wildveilings as gevolg van hul uniekheid en hoë geldlike waarde. Huidiglik is daar meer as 40 kleur variante van Afrika Bovidae. Ondanks die gesogdheid asook die winsgewendheid om met kleur variante te boer, word daar gewaarsku dat kleur variant diere nie ‘n bydrae maak to bewaring nie, aangesien hierdie diere nie normaalweg in die natuur oorleef nie. Gevolglik veroorsaak die opsetlike teel van hierdie diere bekommernis aangesien hulle ‘n bedreiging vir natuurbewaring kan wees. Die doel van hierdie studie was om data in te samel wat besluitneming vir bewaring en die wildbedryf sal vergemaklik. Statistiese analise het gewys dat daar beduidende verskille was ten op sigte van die gedrag van die vier springbok kleur variante wat bestudeer is. Swart springbokke was minder aktief en het meer skadu kolle benut vergeleke met ander kleur variante of normale kleur springbokke. Die donker gekleurde springbokke het ook kleiner oppervlaktes aan die son blootgestel gedurende die warmste deel van die dag as die wit springbokke. Springbokke is ook waargeneem om troppe te vorm gebaseer op fenotipe, waartydens hulle voorkeur getoon het om saam met homogene individue te bly. Hierdie verskynsel is toegeskryf aan die uitstaande prooi effek. Wildveiling omset het die afgelope tien jaar van R62 miljoen na meer as R1 biljoen gegroei. Gepaardgeaande met hierdie groei word rekordpryse ook elke jaar aangeteken. In meeste gevalle behaal wild kleur variante egter baie hoër pryse as die soortgelyke normale kleure. Kleur variante bereik ook groeikoerse wat beter is as inflasie en opbrengste wat beter is as aandele. Selfs al het ‘n normale Kalahari springbok onlangs ‘n rekordprys van R1.2 miljoen behaal word dit steeds ver oortref deur ‘n koffie-kleurige springbok wat teen R4 miljoen verkoop is. Finansiële gewin blyk dan die hoof aansporing te wees vir die handel in kleur variant wild wat gesog geraak het by wildboere. Daar is egter bekommernis onder verskeie belanghebbendes dat die teel van kleur variante wildspesies onvolhoubaar is. Dit is as gevolg van toenemende teenkanting teen die selektiewe teëling van kleur variante asook ‘n gebrek aan belangstelling in kleur variante deur verbruikers wat jagters en eko-toeriste insluit. Geen betekenisvolle bewyse kon tydens hierdie studie gevind word dat daar belangstelling sal wees in die verbruik van kleur variante. Daar is beperkte wetenskaplike data beskikbaar betreffende kleur variante en die meeste inligting wat beskikbaar is, is in die vorm tydskrifte, nuusbriewe en webtuistes. Die beperkte wetenskaplike data wat beskikbaar is aangaande kleur variante het ook gelei tot ‘n debat omtrent hierdie diere. Huidiglik is opinies uiteenlopend en gaan dikwels gepaard met sterk emosionele reaksies van belanghebbendes, veral vanaf wildboere wat voel dat hulle heenkome bedreig mag word deur enige beheermaatreels. Meeste wildboere voel dat hulle toegelaat moet word om met enige dier te boer wat vir hulle die beste opbrengste lewer en aangesien kleur variasie ‘n natuurlike verskynsel is, dit nie ‘n bedreiging vir bewaring inhou nie. Meningsopname resultate het getoon dat, alhoewel baie belanghebbendes gevoel het kleur variante nie ‘n bedreiging vir bewaring is nie, die meerderheid nie die teel van diesulke kleur variante ondersteun nie. Die oorgrote meerderheid belanghebbendes glo dat finansiële gewin die hoof rede is vir die gewildheid van kleur variante. Verskeie belanghebbendes het ook kommer uitgespreek oor die potensieële skade wat kleur variante kan veroorsaak aan Suid-Afrika se bewarings en eko-toerisme beeld aangesien kleur variante veral deur buitelandse jagters as onnatuurlik beskou word. Die uiteindelike gevolgtrekking van hierdie studie is dat die bestaan van kleur variante nie ‘n bedreinging inhou vir bewaring nie, maar dat dit eerder die bestuur van hierdie diere is wat ‘n bedreiging vir bewaring asook vir Suid-Afrika se bewarings beeld inhou.
Keywords: Colour variants; Springbok; Conservation; Game ranching; Bovidae; Behaviour; Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2015